Looking Beyond Panorama of Reaching Schools A Situational Analysis of School-going Adolescent Girls in Jammu (J&K) - Kapoor, Varsha (JOURNAL OF INDIAN EDUCATION, 2022)
Reaching higher levels of education for Indian adolescent girls cannot be a panacea for their empowerment unless the various linked factors are taken care of. This paper critically articulates the impact of socio-cultural settings in getting quality education by adolescent girls in Jammu (India) through gender/ empowerment approach. A division of higher secondary schools is made using quota sampling. Total sample is 300 from twelve schools (240 adolescent girls, 24 parents and 36 teachers). Focussed group discussions (FGDs), observations, questionnaires and structured interviews are the main tools used for data collection. Impact of various factors like socio-cultural environment, issues related to health, parents and teachers as agents of socialisation, safety issues, and decision-making power on getting quality education are analysed. The study emphasizes a holistic approach considering the socio-cultural realities in educational discourse.